eSoulKitchen program - enhancing societal wellbeing and wealth creation for Orang Asli community at Pos Selim, Perak - Ahmad Dahlan, Abdul Rahman; Ibrahim, Jamaludin (2014)
The ethnic label Orang Asli or indigenous people are 'natural people' with unique languages, knowledge systems and beliefs. In 2012, their population is approximately 178,197 or representing a mere 0.9% of 29.7 million people in Malaysia. There are major challenges and issues faced by Orange Asli including in financial, health & nutrition, and education dimensions. This conceptual paper proposes the eSoulKitchen Program, which is to be adapted as one of the Malaysian government-sponsored programs under the leadership of Orang Asli Affairs Department (JAKOA) and the Ministry of Women, Family and Community Development (MWFCD), and implemented as a proof-of-concept in raising the education, economy, health, environmental, and social well-being of Orang Asli community and children in Pos Selim, Perak,Malaysia. eSoulKitchen is primarily an outreach program t o (a) provide nutritional food, (b) ‘feed the soul' with Islamic value, and (c) help generating sustainable new sources of income with new skills, eSoulKitchen Portal and smart partnership.